2006
DOI: 10.1063/1.2178261
|View full text |Cite
|
Sign up to set email alerts
|

Selective electroless plating to fabricate complex three-dimensional metallic micro/nanostructures

Abstract: We report on selective metal deposition over complex polymer structures formed by two-photon induced photopolymerization technique. Periodic three-dimensional micro/nanostructures are fabricated by means of a microlens array to produce multiple spots from a single-beam femtosecond laser. An electroless plating method is used to deposit a thin silver film onto the sample surface. The glass slide surface supporting the structures is chemically modified to avoid silver coating of the substrate. Our technique enab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 19 publications
(18 reference statements)
1
68
0
1
Order By: Relevance
“…Formanek et al demonstrated that silver can be bound to a styrene-modified SCR500 resin that is treated with SnCl 2 after fabrication. [120,121] By making the substrate surface hydrophobic, silver can be reduced selectively onto polymeric microstructures from an aqueous solution. The conductivity of the coating is only about a factor of five lower than that of bulk silver.…”
Section: Chemical Deposition Of Metals On 3d Microstructuresmentioning
confidence: 99%
“…Formanek et al demonstrated that silver can be bound to a styrene-modified SCR500 resin that is treated with SnCl 2 after fabrication. [120,121] By making the substrate surface hydrophobic, silver can be reduced selectively onto polymeric microstructures from an aqueous solution. The conductivity of the coating is only about a factor of five lower than that of bulk silver.…”
Section: Chemical Deposition Of Metals On 3d Microstructuresmentioning
confidence: 99%
“…[119] der Mikrofabrikation mit SnCl 2 behandelt worden war. [120,121] Wenn man die Substratoberfläche hydrophobisiert, kann man Silberionen aus einer wässrigen Lösung selektiv auf den Polymermikrostrukturen reduzieren. Die Leitfähigkeit der Beschichtung ist nur etwa fünfmal geringer als die von makroskopischem Silber.…”
Section: Abscheidung Von Metallen Aus Lösungenunclassified
“…Formanek et al also reported the three-dimensional fabrication of metallic nanostructures over large areas using a combination of two-photo polymerization and electroless plating techniques [15,16]. To fabricate numerous metallic 3D structures for plasmonic metamaterials, multiple laser beam spots created by a micro lens array were introduced to the DLW.…”
Section: Figmentioning
confidence: 99%